Financial Inclusion for Seniors: A Review of Ai-Driven Fintech Interventions - Goswami, Tanya; Goel, Manisha; Malik, Shruti (Journal of Economics and Management, 2026)
Recent progressions within the FinTech space are advancing the way that people receive their financial services globally. Digital finance has improved access, efficiency, and personalization of financial services related to banking, payment, and investment services. However, not all segments of the population have reaped the benefits of these advancements. Older adults are one of the most underserved and at-risk user groups as their usage of digital resources continues to grow within increasingly digitized financial sectors. Older adults face several opt-in barriers attributed to their age, including cognitive decline, low digital literacy and tech anxiety, and trust-related concerns with using a digital service. AI-enabled FinTech solutions such as conversational chatbots, voice-activated applications, biometric users-authentication systems, individually tailored financial recommendations, fraud-detection systems, and adaptable user interfaces represent a significant opportunity to improve the likelihood that seniors will be financially included. The implementation of these types of technological resources can lessen physical, cognitive, and emotional barriers to financial engagement, thus promoting financial independence and confidence. Limited research has been conducted on AI-enabled FinTech from the perspective of older adults; the primary focus has been on consumers in general, and limited attention has been paid to the unique needs and interests of senior citizens. This study will perform a systematic literature review (SLR) of academic, policy, and industry literature on the impacts of AI technology in changing access and increasing confidence in the FinTech sector for senior citizens. The literature reviewed will be categorized into five major areas: accessibility, usability, trust and security, anxiety related to technology, and engagement of consumers in the FinTech marketplace. Overall, findings suggest AI-based tools have the potential to improve both access to and confidence in financial services for seniors, but there continues to be significant gaps related to ethics and design frameworks specific to seniors, long-term trends in adoption of technology, and regulation. Using perspectives from marketing, consumer behaviour, financial inclusion, and information systems, this study will identify critical research gaps and propose pathways for building inclusive, age-friendly, and sustainable AI-based financial ecosystems.